I've already vaguely given you the answer

Algebra Level 5

Let g ( x ) g(x) denote a quintic ( 5 th \big(5^\text{th} -degree ) \big) polynomial such that g ( n ) = 2 n g(n) = 2^n for n = 1 , 2 , 3 , 4 , 5 n = 1,2,3,4,5 and g ( x ) g(x) has a constant term of 5 ! 5! .

Find g ( 6 ) g(6) .


Bonus: Generalize this.


The answer is -56.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Otto Bretscher
Feb 27, 2016

We know that k = 0 n ( 1 ) k ( n k ) g ( k ) = 0 \sum_{k=0}^n(-1)^k{n \choose k}g(k)=0 for any polynomial g ( x ) g(x) of degree < n <n . For n = 6 n=6 this gives g ( 6 ) = g ( 0 ) + k = 1 5 ( 1 ) k + 1 ( 6 k ) 2 k = 5 ! + 2 6 = 56 g(6)=-g(0)+\sum_{k=1}^{5}(-1)^{k+1}{6 \choose k}2^k=-5!+2^6=\boxed{-56}

Moderator note:

Great explanation for how to easily determine the polynomial that approximates an exponential function on several initial values.

Otto, I believe your solution uses quite some tricks, which are not trivial. For example:

k = 1 n ( 1 ) k + 1 ( n + 1 k ) 2 k = 2 n + 1 ( 1 ) n + 1 + 1 + ( 1 ) n \sum_{k=1}^{n}(-1)^{k+1}{n+1 \choose k}2^k = 2^{n+1} (-1)^{n+1} +1+(-1)^n

or: k = 0 n ( 1 ) k ( n k ) g ( k ) = 0 \sum_{k=0}^n(-1)^k{n \choose k}g(k)=0 for any polynomial g ( x ) g(x) of degree < n \lt n , at least not for me, it took me a bit to actually prove this myself. Bringing first equation into a binomial form - it's inviting one to do so - works in fact quite cumbersomely.

Kalis To - 5 years, 3 months ago

Log in to reply

You are right that one of the equations is non-trivial; it was discussed here . Look at @Alan Yan 's elegant solution!

The other equation is just playing around with the binomial expansion of ( 2 1 ) n (2-1)^n .

Otto Bretscher - 5 years, 3 months ago

I think you meant to link this problem instead...

Pi Han Goh - 5 years, 3 months ago

Log in to reply

Either works... the link I provided discusses the case n = 2016 n=2016 , but the two excellent proofs by @Aareyan Manzoor and @Alan Yan cover the general case.

I will post a similar problem that pushes this interesting problem a bit further.

Otto Bretscher - 5 years, 3 months ago

The generalization works here as f ( x ) = 2 x [ ( 1 + x ) ; a t x = 1 ] f(x)= 2^{x}[(1+x); at x= 1] but how does it hold true for any general polynomial of degree < n <n ?

And how is first statement is arrived at is by taking the derivative of a < n <n degree polynomial n n times, What does it mean to substitute x = 6 x= 6 in the equation ?

Vishal Yadav - 4 years, 2 months ago
Zk Lin
Feb 29, 2016

This problem can be tackled by The Method of Differences since the " n n "s are consecutive. Here is the difference table for this question.

n n g ( n ) g(n) D 1 ( n ) D_{1}(n) D 2 ( n ) D_{2}(n) D 3 ( n ) D_{3}(n) D 4 ( n ) D_{4}(n) D 5 ( n ) D_{5}(n)
0 0 120 120 118 -118 120 120 118 -118 120 120 118 -118
1 1 2 2 2 2 2 2 2 2 2 2 118 -118
2 2 4 4 4 4 4 4 4 4 116 -116
3 3 8 8 8 8 8 8 112 -112
4 4 16 16 16 16 104 -104
5 5 32 32 88 -88
6 6 56 \boxed{-56}

Did the same way.

Anupam Nayak - 5 years, 3 months ago
Department 8
Feb 27, 2016

Consider a function f ( x ) f(x) such that f ( x ) = g ( x ) + 2 x f(x)=g(x)+2^x where g ( x ) = a ( x 1 ) ( x 2 ) ( x 3 ) ( x 4 ) ( x 5 ) g(x)=a(x-1)(x-2)(x-3)(x-4)(x-5) where a a is a real number. First note that the constant term of g ( x ) g(x) is -5! on multiplying but we are given that the constant term was 5! so a a must be equal to -1. So g ( x ) = ( x 1 ) ( x 2 ) ( x 3 ) ( x 4 ) ( x 5 ) g(x)=-(x-1)(x-2)(x-3)(x-4)(x-5) , now plugging x = 6 x=6 in f ( x ) f(x) we get 5 ! + 32 = 56 -5!+32=\boxed{-56} .

Thanks to Otto sir:

Here is a way to fix it: With your notation, make f ( x ) = g ( x ) + k = 0 5 ( x k ) f(x)=g(x)+\sum_{k=0}^{5}{x\choose k} = a ( x 1 ) ( x 2 ) ( x 3 ) ( x 4 ) ( x 5 ) =a(x-1)(x-2)(x-3)(x-4)(x-5) , and choose a a so that f ( 0 ) = 5 ! f(0)=5! as required.

@Pi Han Goh, Nice question!, @Otto Bretscher Sorry, if the solution is same as yours.

This is wrong. it is given that f(x) is a polynomial, but f(x) = g(x) + 2^x is not a polynomial

Pi Han Goh - 5 years, 3 months ago

Log in to reply

Actually I wrote f(x) is a function

Department 8 - 5 years, 3 months ago

Log in to reply

But adding 2^x to a polynomial doesn't give you a polynomial.

Amish Naidu - 5 years, 3 months ago

Log in to reply

@Amish Naidu Yes you are right as g(x) is a polynomial but when we add 2^x it becomes a function which is f(x). @Otto Bretscher is the solution right?

Department 8 - 5 years, 3 months ago

Log in to reply

@Department 8 Your f is actually the question's g, which is given to be a polynomial.

Amish Naidu - 5 years, 3 months ago

@Department 8 I must confess that I don't understand your solution. As @Pi Han Goh and @Amish Naidu observe, you are finding f ( 6 ) f(6) , but f ( x ) f(x) is not a polynomial.

Otto Bretscher - 5 years, 3 months ago

Log in to reply

@Otto Bretscher I thought of changing the question so I just created a polynomial that is g(x). Now consider a function which satisfies the property as mentioned in the question that is f(x) then I think you understand what I mean the solution

Department 8 - 5 years, 3 months ago

Log in to reply

@Department 8 The key point is that the function you evaluate at 6 (whatever you name it) is not a polynomial as required in the problem. Also, its value at 0 isn't 5! as required in the problem.

Otto Bretscher - 5 years, 3 months ago

Log in to reply

@Otto Bretscher Oh now I understand what you mean to say thank you

Department 8 - 5 years, 3 months ago

Log in to reply

@Department 8 Here is a way to fix it: With your notation, make f ( x ) = g ( x ) + k = 0 5 ( x k ) f(x)=g(x)+\sum_{k=0}^{5}{x\choose k} = a ( x 1 ) ( x 2 ) ( x 3 ) ( x 4 ) ( x 5 ) =a(x-1)(x-2)(x-3)(x-4)(x-5) , and choose a a so that f ( 0 ) = 5 ! f(0)=5! as required.

Otto Bretscher - 5 years, 3 months ago

Refresh your memory about the definition of a Polynomial .

Calvin Lin Staff - 5 years, 3 months ago

Can you please explain the third and fourth line again. You have taken the constant term 5 ! -5! , but it is given as 5 ! 5!

Chirayu Bhardwaj - 5 years, 3 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...